Working alliance does not mediate the relation between outcome expectancy and symptom improvement following cognitive behavioural therapy for social anxiety disorder. (2019) - Draheim, Amanda A.; Anderson, Page L.
Abstract: A small body of research shows that the working alliance mediates the relation between outcome expectancy and treatment response, but this model has not been applied to the treatment of social anxiety disorder. The present study tests the hypothesis that the working alliance mediates the relation between outcome expectancy and symptom improvement within a randomized controlled trial testing the efficacy of virtual reality exposure therapy for social anxiety disorder. A sample of 54 individuals diagnosed with social anxiety disorder completed eight sessions of virtual reality exposure therapy or exposure group therapy. Participants completed standardized self-report measures of outcome expectancy at the first session, of the working alliance at each session, and three measures of social anxiety symptoms at pre- and post-treatment. The working alliance did not mediate the relation between outcome expectancy and symptom improvement across time points, dependent measures, and treatment type. Bayes factors were calculated for the relation between the working alliance and symptom reduction, while controlling for outcome expectancy and therapist effects. Results were inconclusive. These null findings are intriguing and urge further study of the mechanisms through which common factors relate to treatment response. Utilization of Bayesian analyses may help to clarify the nature of these relations. Key learning aims: (1) Readers will consider the role of common factors in treatment for social anxiety disorder. (2) Readers will learn about how different common factors may interact with each other. (3) Readers will be encouraged to consider how the therapeutic relationship may manifest in a unique manner in treatment for social anxiety.